Finite element method based design and performance analysis of universal motor for agro applications - Sharma, Sudhir Kumar; Manna, Manpreet Singh (Institute of Advanced Engineering and Science, 2023)
A universal motor is one that is capable of operating on either AC or DC power supply. The commutator is a component of the motor that has a significant impact on how efficiently the motor operates. It is essential to conduct an analysis of the pole structure of the universal motor in order to investigate the many aspects. The parametric study of a universal motor with a rating of 1 horsepower and 15,000 revolutions per minute that was designed with various combinations of brush angle and pole embrace factor for use in agricultural applications. The purpose of this study is to improve the effectiveness of the motor while preserving the ideal tolerance range for the model's other parameters as much as possible. The approach now allows for a greater degree of personalization for each distinct combination of factors. With the assistance of the finite element method (FEM), the transient solution is carried out so that the performance of the motor can be evaluated more accurately. The model that has been designed provides major design improvements, one of which is an improved average torque.